Towards the Development of a Device for Assessing the Pliability of Burn Scars - Dalle Mura, Francesco; Governi, Lapo; Furferi, Rocco; Cervo, Marta; Puggelli, Luca (Frontiers in Bioengineering and Biotechnology, 2022)
Burn injuries requires post-accident medical treatment. However, the treatment of burns does not end with first aid because scarred skin must be managed for many years, and in some circumstances, for life. The methods used to evaluate the state of a burn scar based, for instance, on Patient and Observer Scar Assessment Scale or similar ones, often lacks in univocally assessing the scarred skin's state of health. As a result, the primary aim of this research is to design and build a prototype that can support the doctor during scar assessment, and eventually therapy, by providing objective information on the state of the lesion, particularly the value of skin elasticity (also referred as pliability). The developed tool is based on the depressomassage treatment probe named LPG, currently used to treat burn scars in a number of hospitals. It is a non-invasive massage technique using a mechanical device to suction and mobilize scar tissue. It is used as a post-operative treatment to speed up the healing process to make the mark of the scar less visible. The prototype is specifically designed to be manufactured using Additive Manufacturing and was validated comparing its performances against the ones of a certified instrument (i.e. the Romer Absolute ARM with RS1 probe). Validation was carried out by designing and developing a tool to put the RS1 probe in the same measurement conditions of the new prototype probe. Tests performed to assess the performance of the devised prototype show that the probe developed in this work is able to provide measurements with a sufficient degree of accuracy (maximum error ± 0.1 mm) to be adopted for a reliable estimation of the elasticity value in a hospital environment.